Perancangan Peningkatan Kinerja Menggunakan Metode Analitycal Hierarchy Process: Studi Kasus Industri Perekat - Wibowo, Anak Agung; Sukarma, Lukman (Universitas Pamulang, 2024)
The adhesive industry located in Bogor is a company engaged in the manufacturing and trading of adhesive products (glue) as well as polymer-based products. Has a factory and warehouse located in Cibinong Bogor, which not only produces but also serves as a distribution center for goods from the adhesive industry. Having a warehouse for final goods, warehouse for storing production products, has a long processing time in the work process, this is due to a lack of orderly placement of goods resulting in delays in the work process. The first step taken is calculating the time of each standard contained in the FG warehouse (Finished Goods), so that the time for each process is obtained, it can be seen that the weight in each process can be seen using the KPI (Key Performance Indicator) weighting. Then the classification using AHP (Analytical Hierarchy Process), after normalizing with S-Norm and it can be seen that the KPIs included in the green category are 10 KPIs, 5 KPIs in yellow category, and 5 KPIs in red which are known to have a tendency of problems. In the work chain process at FG's warehouse, Fishbone analysis is then carried out and input can be determined for improvement as a final step.